Grain price seasonality in Kebbi state, Nigeria - Hatzenbuehler, Patrick L.; Mavrotas, George; Maikasuwa, Mohammed Abubakar; Aliyu, Abdulrahaman (International Food Policy Research Institute, 2018)
Recent studies on food prices in sub-Saharan Africa (SSA) found that food price seasonality in SSA remains an issue. In addition to it causing price risk, and, hence, limiting market participation among farmers and traders, the continued existence of substantial price seasonality implies that interventions that improve food market development are needed. Using a dataset that is unique for Nigeria, we contribute to this literature through measurement of the extent of seasonality in grain prices in a set of markets in Kebbi state. We believe that our focus on seasonality at the state, rather than country or continental, level can provide needed insights that are useful for identification of areas deserving stakeholder focus for rural development related initiatives. A main contribution is that we find that there are large enough differences in price behavior across the assessed markets to justify this more localized analysis.